Psychological Assessment in Transit – Scientific Production of the Last 10 Years - Fiori, Lidiane Gabbi; Gonçalves Caneda, Cristiana Rezende (Revista de Psicologia da IMED, 2014)
Despite the psychological evaluation to acquire driver's license has been instituted by the Brazilian government a few decades, research in the area are not sufficient. This study performed a systematic literature review to identify the scientific literature on the psychological assessment of transit in the last ten years, on the basis of PePSIC, SciELO and LILACS. To access the publications, we used the descriptors: psychological evaluation in traffic. The survey selected 14 articles considered relevant in this study. From these studies, frequency analysis of articles published on the indexes, instruments used in research, origin and affiliation of the studies were conducted. The results indicated that scientific production has grown in the last decade and demonstrates the interest of researchers for psychometric instruments. Most of these privilege the cognitive area and scales of symptoms. Still perceived the lack of instruments to assess personality traits of drivers. Most studies were developed by San Francisco University of São Paulo. Finally there was a dearth of research in the area, especially when the established criteria by CONTRAN.